1987
DOI: 10.1038/clpt.1987.71
|View full text |Cite
|
Sign up to set email alerts
|

Ketorolac tromethamine as compared with morphine sulfate for treatment of postoperative pain

Abstract: Ketorolac tromethamine, a nonnarcotic, prostaglandin synthesis-inhibiting analgesic, was compared with morphine sulfate for relief of moderate to severe postoperative pain. The 155 patient participants received single intramuscular doses of either ketorolac, 10, 30, or 90 mg, or morphine, 6 or 12 mg, administered in a double-blind, randomized fashion. Pain scores (verbal and visual analog) were recorded at baseline and assessed at 30 minutes and then hourly to 6 hours. Pain relief was rated at the same times. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(61 citation statements)
references
References 0 publications
1
58
0
2
Order By: Relevance
“…It is a non-steroidal anti-inflammatory drug (NSAID) with proven efficacy in the management of moderate to severe postoperative pain. [1][2][3] Ketorolac can be administered orally, parenterally, or topically 4 either alone or in combination with opioids. When used as an adjunct, there may be a 25-50% reduction in opioid requirements, which may reduce the incidence of adverse side effects associated with opioid consumption.…”
Section: Résumémentioning
confidence: 99%
“…It is a non-steroidal anti-inflammatory drug (NSAID) with proven efficacy in the management of moderate to severe postoperative pain. [1][2][3] Ketorolac can be administered orally, parenterally, or topically 4 either alone or in combination with opioids. When used as an adjunct, there may be a 25-50% reduction in opioid requirements, which may reduce the incidence of adverse side effects associated with opioid consumption.…”
Section: Résumémentioning
confidence: 99%
“…COX inhibitors are, however, very efficient drugs in the treatment of postoperative inflammation and pain in orthopaedic trauma and surgery. Several studies have proven their superior effects compared to other analgesics like acetaminophen, codeine, and opioids [10,11,25,44,48]. It has been demonstrated that the analgesic and antiinflammatory effects of conventional COX inhibitors are attributed to the inhibition of COX-2, which is the COX isoform involved in the induction of pain and inflammation [18,57].…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Ketorolac tromethamine is a parenterally active and potent NSAID with an analgesic efficacy comparable to approximately 12 mg of morphine. 9 Its topical administration has been shown to be as effective as systemic administration in mastectomies 10 and more effective when infiltrated locally in inguinal hernia repair.…”
mentioning
confidence: 99%